Students’ Speaking Anxiety and its Effect on Speaking Performance Based on their Gender - Wahyu Istiqomah (Universitas Negeri Surabaya, 2024)
One of the skills that must be mastered by students is speaking English. However, not all students have confidence in speaking English in front of many people. Both female and male students can feel speaking anxiety which will affect their speaking performance. This study was conducted on 12th grade high school students. Therefore, the aim of this study is to determine the speaking anxiety level of each gender, the relationship between speaking anxiety and speaking performance, and the factors that influenced speaking anxiety in each gender. This research uses quantitative research with correlation studies. Female students proved to be more confident to speak English than male students. In addition, speaking anxiety has a very high relationship with speaking performance. That means, speaking anxiety greatly affects speaking performance for both female and male students. Furthermore, female students experience speaking anxiety as a result of test anxiety, whereas male students experience speaking anxiety as a result of communication apprehension, test anxiety, and fear of negative evaluation.